Analisis Penerapan Integrated Marine Information System (IMAIS) Pada PT Pelindo Marine Service - Zahra Nur Annisa; Zsa Zsa Izazi (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
In a business context, the implementation of information systems is very important both inside and outside the company. This study aims to evaluate the implementation of an Integrated Marine Information System (IMAIS) based information system at PT Pelindo Marine Service. The research method used is a descriptive qualitative approach, where the author explains the problems faced and describes how the management information system is implemented at PT Pelindo Marine Service, as well as evaluating it based on existing theory. The research results show that PT Pelindo Marine Service has succeeded in implementing the information system well. A thorough evaluation needs to be carried out on aspects of data availability, suitability to business needs, regulatory compliance, operational efficiency, usage and service quality. Regular system updates are important for relevance to developing needs. System flexibility in the face of changing business environments depends on continuous evaluation to ensure effectiveness.